2012
DOI: 10.1371/journal.pone.0047311
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gap Junction Protein Connexin43 in Astrogliosis Induced by Brain Injury

Abstract: Astrogliosis is a process that involves morphological and biochemical changes associated with astrocyte activation in response to cell damage in the brain. The upregulation of intermediate filament proteins including glial fibrillary acidic protein (GFAP), nestin and vimentin are often used as indicators for astrogliosis. Although connexin43 (Cx43), a channel protein widely expressed in adult astrocytes, exhibits enhanced immunoreactivity in the peri-lesion region, its role in astrogliosis is still unclear. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 79 publications
(118 reference statements)
6
55
1
1
Order By: Relevance
“…63 We previously showed that the upregulation of Cx43 occurs mostly in glial fibrillary acidic protein (GFAP)-expressing reactive astrocytes and not in microglia or NG2 oligodendrocyte progenitors. 19 Reactive astrocytes are one of the major cell types found in gliomas 2,3,64 and they are often indistinguishable from glioma cells in pathological samples. 64 In fact, we observe enhanced Cx43 immunoreactivity only in a sub-population of tumor-associated astrocytes that are closest to the tumor cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…63 We previously showed that the upregulation of Cx43 occurs mostly in glial fibrillary acidic protein (GFAP)-expressing reactive astrocytes and not in microglia or NG2 oligodendrocyte progenitors. 19 Reactive astrocytes are one of the major cell types found in gliomas 2,3,64 and they are often indistinguishable from glioma cells in pathological samples. 64 In fact, we observe enhanced Cx43 immunoreactivity only in a sub-population of tumor-associated astrocytes that are closest to the tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…19 Some evidence suggests that the glial scar acts as a barrier to constrain invasive tumor cells. 73 To determine whether there is a correlation between the extent of astrogliosis and glioma invasiveness, we examined the degree of gliosis by measuring the distance from the tumor periphery to a region of brain parenchyma with no detectable level of GFAP immunoreactivity.…”
Section: Attenuated Glioma Invasion In the Presence Of Truncated Astrmentioning
confidence: 99%
See 1 more Smart Citation
“…In astrocytes, they are composed of connexins 30 and 43 (Cx30, Cx43) [66]. Cx43 is widely expressed in adult astrocytes and exhibits increased expression in reactive astrocytes induced by various brain pathologies and intercellular calcium signaling [67][68][69][70][71][72][73]. Also, Cx43-mediated intercellular communication between astrocytes plays an important role in the invasion of glioma cells in the brain [63].…”
Section: Astrocytes' Direct Cell-cell Interactions With Tumor Cellsmentioning
confidence: 99%
“…An upregulation or downregulation of Cx43 expression has been observed in reactive astrocytes, while activated microglia are primarily characterized by an induction of Cx43 expression [98,194,[350][351][352][353][354][355][356][357][358][359][360][361]. However, treatments that suppress Cx43-based communication can have different outcomes, i.e., they have been reported to be neuroprotective [337,[362][363][364] as well as neurotoxic [365,366] in different models of neurodegenerative conditions.…”
Section: Contribution Of Astroglial Connexins To Vasomotor Control Anmentioning
confidence: 99%